Effects of a video education program for patients with benign uterine tumors receiving high-intensity focused ultrasound treatment - Mi Suk Hong; Hyoung Sook Park; Young Suk Cho (Korean Society of Women Health Nursing, 2020)
Purpose The purpose of this study was to examine the effects of a video education program in women receiving high-intensity focused ultrasound (HIFU) treatment. Methods This was a quasi-experimental study with a nonequivalent control group non-synchronized design. The participants were 54 patients who had benign uterine tumors and adenomyosis. The data were collected from June to August 2018. A 10-minute video education program on HIFU and post-procedural care was developed based on the literature. The experimental group was provided the video education program with a question-and-answer session for 10 minutes after viewing the video. The control group received usual care (i.e., verbal instructions on post-procedural self-care). The questionnaire survey was conducted twice: before the educational program and before being discharged from the hospital. Differences in uncertainty, emotions, and self-efficacy among patients were analyzed. Data were analyzed using the chi-square test, Shapiro-Wilk test, paired t-test, and t-test with SPSS version 23.0. Results The participants in the experimental group showed a decrease in uncertainty(t=4.33, p<.001), improvements in anxiety(t=-4.07, p<.001) and depression (t=-3.55,p<.001), and an enhancement ofself-efficacy (t=-4.39,p<.001) compared to the control group. Conclusion This nursing intervention was effective at reducing uncertainty, improving emotions, and enhancing self-efficacy. This intervention is feasible for use in nursing practice as an aid for patients when considering treatment methods.